(untitled) (Journal of EAHIL, 2025)
CABI Global Health is a specialized bibliographic database for public health research, developed by CABI, a not-for-profit organization addressing global health challenges. It contains nearly 5 million curated records from peer-reviewed journals, grey literature, and multidisciplinary sources, offering comprehensive coverage of public health issues worldwide. Beyond traditional medical disciplines, it integrates One Health, environmental health, nutrition, and zoonotic diseases, emphasising the interconnectedness of human, animal, and environmental health. The database’s indexing system, including the CABI Thesaurus and CABIcodes, ensures precise literature retrieval. Committed to global knowledge representation, CABI actively indexes research from underrepresented regions, particularly low- and middle-income countries. Available via the CABI Digital Library, EBSCO, Web of Science, and Ovid, CABI Global Health is a vital resource for researchers, policymakers, and practitioners engaged in evidence-based public health decision-making.